Organic Agriculture - Andrzej Klimczuk; Magdalena Klimczuk-Kochańska (The Palgrave Encyclopedia of Global Security Studies, 2020)
Consumers are increasingly aware of the health- and safety-related implications of the food which they can buy in the market. At the same time, households have become more aware of their environmental responsibilities. Regarding the production of food, a crucial and multifunctional role is played by agriculture. The way vegetables, fruits, and other crops are grown and how livestock is raised has an impact on the environment and landscape. Operations performed by farmers, such as water management, can be dangerous for the soil and the whole ecosystem. Consequently, there is a search for natural ways of sustaining the impact of agriculture on the environment. In this context, one of the most popular ideas is organic agriculture. In the literature on the subject, there are many concepts that some authors consider to be synonymous even as others argue that these terms are not interchangeable. There is, for example, "organic agriculture," "alternative agriculture," "sustainable agriculture," "ecological agriculture," "biological agriculture," "niche farming," "community-supported agriculture," and "integrated pest management." Very often, techniques and products related to organic agriculture are described by marketing experts with the use of abbreviations such as "bio" and "eco." Products with such markings and labels are increasingly popular in stores that often give them separate shelves for their sale. Despite the higher price compared to conventional products, they are increasingly sought by consumers. The entry examines the various impacts of organic agriculture with a view to these trends.
Keywords: O13; Q01; Q18; 630; Alternative agriculture; Biological agriculture; Ecological agriculture; Sustainable agriculture; Niche farming